Double Fano resonances in an individual metallic nanostructure for high sensing sensitivity. (31st October 2017) - Yan, Zhendong; Wen, Xiangmin; Gu, Ping; Zhong, Huang; Zhan, Peng; Chen, Zhuo; Wang, Zhenlin
Abstract: In this paper, we report on the design and observation of double Fano resonances (DFRs) in an individual symmetry-reduced nanostructure and the induced high sensing sensitivity. Such a plasmonic nanostructure consists of a partially overlapped double-metallic nanotriangles with unequal sizes fabricated by using fast and low-cost angle-resolved nanosphere lithography. Symmetry breaking generates two narrow quadrupolar dark modes, which further enhance the coupling with fundamental bright dipole modes within the same structure, manifesting the effect of DFRs. The resonance wavelength and line shape of DFRs can be tailored by changing the degree of asymmetry as well as the size of the designed nanostructure. Based on DFRs, a high sensitivity to dielectric environment with a maximum figure of merit of 35 is measured. Due to a fast manufacturing process with high reproducibility and high structural tunability, the fabricated individual metallic nanostructure provides an opportunity for significant potential applications in localized surface plasmon resonance based single or double-wavelength sensors in the near-infrared region.